Employed Yet Still Poor: A Microdata Analysis of Working Poverty in Indonesia - Setyanti, Axellina Muara; Syafitri, Wildan; Finuliyah, Firdaus; Khoiruddin, Muhammad Afif (Jurnal Ketenagakerjaan, 2024)
This study aims to quantify the extent of working poverty in Indonesia and identify the demographic, geographic, and occupational factors associated with it, using microdata from the Survei Sosial Ekonomi Nasional (SUSENAS) 2022. The analysis employs logistic regression to determine the key determinants of working poverty among Indonesian laborers. The results reveal that older individuals, males, those with bank accounts, and those who use telephones and the internet are less likely to be in working poverty. These findings highlight the importance of age-related experience, gender-related economic advantages, financial inclusion, and digital connectivity in mitigating working poverty. Notably, education and formal sector employment did not show significant effects, suggesting that other factors may mediate their relationship with working poverty. The results emphasize the need for policies promoting financial and digital inclusion as part of poverty alleviation strategies. Enhancing access to banking services, telecommunication, and the internet, along with addressing gender disparities in the labor market, is crucial. Further exploration into the quality and market relevance of education is also recommended to design effective interventions tailored to the diverse needs of the working poor.